2017
DOI: 10.1136/bmjopen-2016-015812
|View full text |Cite
|
Sign up to set email alerts
|

Are thyroid nodules associated with sex-related hormones? A cross-sectional SPECT-China study

Abstract: ObjectiveLittle is known about the association between thyroid nodules (TNs) and endogenous sex hormones. We aimed to investigate the relationship between TNs and sex-related hormones among men in China.SettingThe data were obtained from a cross-sectional study Survey on Prevalence in East China for Metabolic Diseases and Risk Factors (SPECT-China study, 2014–2015) based on the population.ParticipantsIn total, 4024 men over 18 years of age who were not using hormone replacement therapy and who underwent comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…The cause of this increased risk in females is unclear, although estrogen and progesterone may contribute to this difference in incidence 17. However, the findings in this study conflicted with those of Chen Y et al, who reported that TNs were more prevalent in males in China 18…”
Section: Discussioncontrasting
confidence: 95%
“…The cause of this increased risk in females is unclear, although estrogen and progesterone may contribute to this difference in incidence 17. However, the findings in this study conflicted with those of Chen Y et al, who reported that TNs were more prevalent in males in China 18…”
Section: Discussioncontrasting
confidence: 95%
“…Differences in the iodine nutrition status and definition of thyroid nodules between these two studies may also partially explain the discrepancy in the results. The SPECT-China study found a 41.4% prevalence of thyroid nodules, similar to our result ( 27 ). The prevalence in Shanghai in 2009 was 27.76% ( 28 ), and in Heilongjiang Province in 2018, it was 36.88% ( 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…Estradiol is considered a potent growth factor both for benign and malignant thyroid cells (37)(38)(39). Men with TNs show reduced levels of testosterone and sex hormone-binding globulin (SHBG) (40). The gender disparity observed in the association of chronic-MetS with the risk of TNs may be due to the different impact of MetS on endogenous sex hormones.…”
Section: Discussionmentioning
confidence: 99%